Effects of systemic octreotide, local mytomycine-C and local corticosteroids on wound-healing reaction after glaucoma surgery - Akyol, Nuray; Demir, Tamer; Kükner, Aysel; Çolako?lu, Neriman (My University, 2001)
Purpose: To determine and compare the effectiveness of octreotide, mitomycine-C and corticosteroids on wound-healing reaction after glaucoma surgery. Methods: A full thickness scleral trephination was carried out by the same surgeon on tour groups of six rabbits. A sponge soaked in mytomicine-C was applied subconjunctivally in group 1 before trephination. Group 2 received corticosteroid drops tid topically for 14 days. Group 3 received subcutaneous octreotide injections tid for 14 days. The control group (group 4) was not given any drug that may interfere with wound healing. All groups received gentamycine drops tid for seven days. The rabbits were Sacrificed on the fourteenth day and the trephination area with overlying conjunctiva was excised. The samples were prefixed with glutaraldehyde, dehydrated and embedded in Araldite Cy 212. Ten semithin sections stained with toluidin blue were analysed for each group. Fibroblast and macrophage counts were performed on the surgical site and subconjunctival area. Results: Intensive fibroblastic activity, increased number of vessels and active macrophages were observed only in group 4. The fibroblast and macrophage densities in this group were significantly higher than the other three groups in which wound healing was modulated (p < 0.001). Mean number of fibroblasts in group 1 was also significantly less than the ones of groups 2 and 3 (p < 0.01). Macrophage densities were similar in groups 1, 2 and 3. No statistical significance was found between groups 2 and 3 by means of fibroblast and macrophage densities. Conclusion: Octreotide reduced wound-healing reaction in a similar fashion to corticosteroids or mitomycine-C. These initial results seem promising.
Keywords: Glaucoma filtration surgery; Octreotide; Wound healing modulation